Tumor biopsy and patient enrollment in clinical trials for advanced hepatocellular carcinoma - Rimassa, Lorenza (BAISHIDENG PUBLISHING GROUP INC, 2017)
Tumor biopsies may help to reliably distinguish hepatocellular carcinoma (HCC) from other tumors, mostly cholangiocarcinoma as well as to identify the patient populations who most benefit from target-driven HCC treatments, in order to improve the success rate of experimental therapies. Clarifying tumor biology may also lead to identify biomarkers with prognostic role and/or enabling to predict response or resistance to therapies. Recently, clinical trials have more efficiently included biomarker endpoints and increasingly collected tumor tissue from enrolled patients. Due to their frail status and sometimes fast-progressing disease, the performance status of patients with HCC progressing on first-line therapy can deteriorate quickly, preventing their enrollment in clinical trials. However, the challenge of identifying the proper patient at the proper time can be overcome by periodic inter-department meetings involving the key specialists taking care of HCC patients, and solid networks between research centers and referring institutions. An early planned biopsy would also facilitate timely inclusion of patients in biology-driven clinical trials. Ultimately, institution of multidisciplinary teams can optimize treatment choice, biopsy timing, and quick enrollment of patients in clinical trials, before their performance status deteriorates.